Dziennik Bridget Jones - Fielding, Helen, 1958-; Naczynska, Zuzanna (Poznan : Zysk i S-ka, 2001)
Polish translation of "Bridget Jones' Diary". A humorous novel about a single girl in England.
Translation of: Bridget Jones's diary.
Keywords: Jones, Bridget (Fictitious character) -- Fiction; Single women -- England -- Fiction